In-vitro antigonococcal activity of rosoxacin (WIN 35213). Issue 1 (February 1981) - Warren, C A; Shannon, K P; Phillips, I
Abstract : The in-vitro activity of rosoxacin against 173 isolates of Neisseria gonorrhoeae, including 17 beta-lactamase-producers, was tested by an agar dilution method. Of the isolates, 167 (including 16 of the beta-lactamase-producers) were inhibited by 0 . 06 mg/l of rosoxacin. The remaining six isolates, one of which produced beta-lactamase and the others were moderately resistant to penicillin, were inhibited by 0 . 12-0 25 mg/l of the compound. There was little correlation between the minimum inhibitory concentrations (MICs) of rosoxacin and penicillin, except for isolates with MICs of penicillin of 0 . 06-1 mg/l, for which correlation was good.